2009
DOI: 10.3233/jad-2009-0931
|View full text |Cite
|
Sign up to set email alerts
|

False Recognition Correlates with Amyloid-β1–42 but not with Total Tau in Cerebrospinal Fluid of Patients with Dementia and Mild Cognitive Impairment

Abstract: Severe memory impairment forms the core symptom of Alzheimer's disease (AD), which is present early in the disease course. Recent studies show that AD patients not only suffer from forgetfulness, but also differ in their response bias, when having to decide whether information has been perceived recently, or whether it is only familiar or semantically related to perceived information. Changes in total tau-protein and amyloid-beta (Abeta) (1-42) concentration in cerebrospinal fluid are also features of AD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Hildebrant et al, 2009aHildebrant et al, , 2009bYeung et al, 2013). In this way findings from several experimental paradigms provide concurrent evidence that false recognition (and false memories) increases with age in healthy older people (e.g.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Hildebrant et al, 2009aHildebrant et al, , 2009bYeung et al, 2013). In this way findings from several experimental paradigms provide concurrent evidence that false recognition (and false memories) increases with age in healthy older people (e.g.…”
Section: Introductionmentioning
confidence: 67%
“…For this reason, it seems reasonable to suppose that a significant decline in false recognition in older people could be considered another early marker of cognitive impairment (e.g. Hildebrant et al, 2009aHildebrant et al, , 2009b because it would indicate a significant deficit in their gist memory. The fact that young people and AD patients do not differ on their false recognition rates is probably due to two different causes: as we mentioned above, young people show a low rate of false recognition because they correctly use the recall-to-reject strategy to reduce their false alarm rates, while the AD patients show low false recognition rates because they show an overdependence on their impaired gist memory (Gallo et al, 2006;Hudon et al, 2006).…”
Section: Young (N ¼42)mentioning
confidence: 99%
“…Stomrud and collaborators [17] showed that a low level of Aβ 1−42 is correlated with a decline in the MMSE score three years later in healthy elderly subjects. We have also found that Aβ 1−42 and not tau protein correlates with memory functions [22]. This would suggest that Aβ 1−42 still declines in CSF during the clinical phase of amnesic MCI, which would be highly relevant for the early identification of AD patients.…”
Section: Introductionmentioning
confidence: 74%
“…Introducing word list recognition performance from the CERAD-NP, the sensitivity of the AD diagnosis increased considerably (97%), but the specific- ity still ranged between 48 and 82%. Using a false recognition test with pictures of semantically related items [22] , led to an increase of the sensitivity of the diagnosis (100%) and to an acceptable level for the specificity (about 90% for the 3 different other types of dementia). For the MCI patients, the impact of false recognition on the sensitivity was not as great as for the 4 dementia groups.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from our recognition task, which has been demonstrated to be sensitive to beta-amyloid concentration in the cerebrospinal fluid (CSF) [22] , we used an established neuropsychological instrument for assessing dementia patients, the CERAD-NP [23] , and focused on the word list saving score, because this score measures the degree of forgetting following distraction. As mentioned above, 2 recent reviews on neuropsychological assessment in dementia [1,2] showed that fast forgetting after a delay or after distraction is a core feature of AD.…”
mentioning
confidence: 99%